The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1029/2000jd900611
|View full text |Cite
|
Sign up to set email alerts
|

Bromine oxide—ozone interaction over the Dead Sea

Abstract: Abstract. Atmospheric measurements were performed during a 1 month period in early summer of 1997 at the Dead Sea in Israel in an attempt to identify bromine monoxide BrO, and evaluate its effect on ozone chemistry. The differential optical absorption spectroscopy (DOAS) technique was utilized to identify and measure BrO present in the air masses. Concurrent to the DOAS measurements, continuous monitoring of SO2, NO/NOx, O3, and CO was performed. Filter samples for aerosol analysis and whole air canister sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 43 publications
(1 reference statement)
4
90
2
Order By: Relevance
“…Hebestreit et al (1999) and Matveev et al (2001) were able to detect very high mixing ratios of up to 176 pmol/mol BrO over the Dead Sea, Israel (ISR97-G) with LP-DOAS. Compared to the open ocean, however, the Dead Sea has a much higher bromide content and is also acidic with a pH<7 (Nishri and Stiller, 1997), which favors heterogeneous reactions releasing bromine (see also Sects.…”
Section: Inorganic Gas-phase Bromine Speciesmentioning
confidence: 99%
“…Hebestreit et al (1999) and Matveev et al (2001) were able to detect very high mixing ratios of up to 176 pmol/mol BrO over the Dead Sea, Israel (ISR97-G) with LP-DOAS. Compared to the open ocean, however, the Dead Sea has a much higher bromide content and is also acidic with a pH<7 (Nishri and Stiller, 1997), which favors heterogeneous reactions releasing bromine (see also Sects.…”
Section: Inorganic Gas-phase Bromine Speciesmentioning
confidence: 99%
“…An overview of the hitherto detected mixing ratios of RHS in the lower troposphere is given in Table 1. IO could contribute to Matveev et al (2001), Salt Lake City, Caspian Sea, Wagner et al (2001), Stutz et al (2002), Salar de Uyuni) Hönninger et al (2004a) BrO Antarctic, Arctic 30 - Hausmann and Platt (1994), Tuckermann et al (1997), Hegels et al (1998), Martinez et al (1999), Hönninger et al (2004b) (Cox et al, 1999) b σ OIO (548.6 nm)=1.1×10 −17 cm 2 (Bloss et al, 2001) ozone destruction in a manner comparable to BrO, even in low mixing ratios. Additionally, recent field and laboratory studies indicate that reactive iodine plays an important role in new particle formation processes (Hoffmann et al, 2001;O'Dowd et al, 2002;Jimenez et al, 2003;Burkholder et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…26 The bromine-related reactions used are given in Table 3. The rate constants are given in units of cm 3 , molec, and sec. All photolysis constants are relative to NO 2 photolysis (i.e., k 1 ), and the NO 2 photolysis rate shown in Table 3 is the measured value for the environmental chamber experiments.…”
Section: Simulations Of Datamentioning
confidence: 99%
“…1 Several recent studies have implicated bromine-containing compounds with observed local ozone reductions. [2][3][4] However, these observations have often involved interactions with either chlorine or heterogeneous surfaces. Also, the atmospheric conditions of these observations (e.g., in Arctic areas or the Dead Sea) were not typical of the conditions associated with urban smog formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation